Thecoperitoneal Shunts—Our 20 Years Experience - Kirit Arumalla; Naseer Mohammed; Dhananjaya I Bhat; Dhaval Shukla; B. Indira Devi (Indian Journal of Neurosurgery)
Introduction The thecoperitoneal shunt is a modality of cerebrospinal fluid (CSF) diversion used to treat various clinical conditions such as idiopathic intracranial hypertension (IIH), normal pressure hydrocephalus (NPH), and CSF leaks. There is a wide variability in the data regarding the utility and complications associated with it. We thus reviewed the outcomes and complications of the shunt done in our setting.